ChemInform Abstract: A General Method for N‐Methylation of Amines and Nitro Compounds with Dimethylsulfoxide. Issue 25 (24th June 2014) - Jiang, Xue; Wang, Chao; Wei, Yawen; Xue, Dong; Liu, Zhaotie; Xiao, Jianliang
Abstract A novel, green, and practical method for the amine methylation is developed.